CHRISTIAN LEADERSHIP FUNCTIONS IN CORINTH AND EPHESUS: A STUDY IN HISTORICAL CONTEXTS - Frim, Jennifer (My University, 2018)
This study contains a thick description of the early Christian communities in Corinth and Ephesus, demonstrating the unique context of each. It explores the Greco Roman context, the historic context of the emergence of Christianity in each city, and the immediate context of the writing of each of the Pauline letters under investigation. It then uses those descriptions as a lens through which to examine the discussion of Christian leadership functions in 1 Cor 12:27-31, Eph 4:1-16, and 1 Tim 3:1-13. By employing methods of social description in an analysis of the Christian communities in Corinth and Ephesus, this study has demonstrated that Paul's discussion of specific leadership functions with respect to each city is rooted in the historical context of each Christian community and therefore Paul mentions leadership functions and promotes attitudes concerning leadership which are in keeping with the circumstances of each community and does not necessarily promote uniform practice in all places. Ultimately, 1 Cor 12:27 31 discusses the primary importance of the leadership functions of apostle, prophet, and teacher in building up the Christian church, rather than the gifts of tongues that the Corinthians had been elevating to the highest positions. Ephesians 4:1-16 describes the leadership functions of apostle, prophet, evangelist, and pastor and teacher as gifts from God whose purpose is training the saints, doing works of service, and building up the body of Christ. These leaders are to promote unity in a divided Ephesian church. Finally, 1 Tim 3:1-13 describes qualities for those wishing to fulfill the leadership functions of overseer and deacon (men and women). These qualities are designed to combat false teachers in the midst of the Christian community in Ephesus which had a long history of difficulties.
Keywords: Corinth; Ephesus; early Christian communities; Pauline letters